TRANSFORMASI PENGETAHUAN, PERILAKU DAN PERSEPSI REMAJA TENTANG BAHAYA ROKOK ELEKTRIK MELALUI PENYULUHAN MEDIA VISUAL: STUDI PRA DAN PASCA INTERVENSI - Ferdy Ari Ananda, I Wayan; Khasanah, Nur; Rohmah, Khaula Lutfiati; Herliana Riska; Najmatul Rahmi Widadi (STIKes Mitra Husada Medan, 2025)
Background: The long-term use of electronic cigarettes has been shown to cause adverse effects on health. The substances contained in electronic cigarettes have increased the risk of lung diseases. Method: This study employed a quantitative research method with a quasi-experimental design, utilizing purposive sampling that involved 32 adolescents and parents as participants. Data were collected through pre-tests and post-tests regarding knowledge, behavior, and perceptions before and after providing education using visual media. Data analysis was conducted using the Wilcoxon test. Results: The results indicated that the educational method using visual media was effective in improving knowledge, but there was no improvement in the variables of behavior and perception. Conclusion: The use of the educational method with visual media was only effective in enhancing knowledge, with no increase observed in behavior and perception variables.